Morphological Characterization of Amaranth (Amaranthus hybridus L.) Accessions from Urban and Peri-Urban Market Gardening of Abidjan and Yamoussoukro - Jean-Claude N’zi; Christophe Kouame; Vonogo Nikodeme Kabre; Lassina Fondio; Edith Agbo; Adolphe Mahyao (European Scientific Journal, ESJ, 2026)
This work focuses on the morphological characterization of eighteen amaranth (Amaranthus hybridus) accessions collected in urban and peri-urban market gardening of Abidjan and Yamoussoukro in Côte d'Ivoire. These accessions were regenerated and multiplied at the Experimental and Production Station of the National Center for Agronomic Research in Anguédédou. This study was conducted using a Fisher block design with three replicates. Quantitative and qualitative variables were observed and measured for each of these accessions. Collected data were submitted to analysis of variances and multivariate analyses (PCA) to discriminate variables. Results showed a high variability for each of the nine (09) quantitative variables and for some of the fifteen (15) qualitative variables studied. The green morphotypes showed the strongest performance in terms of leaf biomass (29 leaves per plant), stem diameter (5.9 cm), plant height (137 cm) and panicle length (48.7 cm). These data confirm morphological variability within the population of A. hybridus studied could be used in a selection program for the improvement and sustainable cultivation of this foodstuff in Côte d'Ivoire.